Malaysians perception on code-switched advertisement / Shairah Hana Sulaiman, Muhamad Izzat Rahim and Mohamad Hanis Yahaya - Sulaiman, Shairah Hana; Rahim, Muhamad Izzat; Yahaya, Mohamad Hanis (Universiti Teknologi MARA, Negeri Sembilan, 2013)
Despite the various researches conducted on the impact of code switching in the marketing field, little is known about the impact of code switching between Bahasa Malaysia and English in advertisements. Therefore this study intended to investigate the impact of usage of code switching between these two languages in advertisements. Local students studying in local universities were used as the target group (N=30). The aims of this study were to investigate the attitude towards such advertisements, the reasons behind the perceptions and the impact of such advertisement on its persuasion level. It was found that the respondents have positive perceptions towards code-switched advertisements. Hence, the findings suggest that code switching is a good marketing skill as it is perceived as effective, influential and creative.